An analytic approach for pricing American options with regime switching - Leunglung Chan; Song-Ping Zhu (Journal of Risk and Financial Management, 2021)
This paper investigates the American option price in a two-state regime-switching model. The dynamics of underlying are driven by a Markov-modulated Geometric Wiener process. That means the interest rate, the appreciation rate, and the volatility of underlying rely on hidden states of the economy which can be interpreted in terms of Markov chains. By means of the homotopy analysis method, an explicit formula for pricing two-state regime-switching American options is presented.
Keywords: 330; free boundary problem; homotopy analysis method; option pricing; regime switching